Implementasi Linked List pada Interaksi Antar Marker Augmented Reality untuk Operand dan Operator Aritmetika - Hermawan Wijaya; Wibisono Sukmo Wardhono; Issa Arwani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Augmented Reality (AR) refers to a direct perception of the surrounding environment that has been added to the virtual component of the computer. There is generally no default mechanism for storing sequences in the AR framework, which in this context is Vuforia SDK. Linked List is one of the methods in Algorithm and Data Structure used to organize data structures in a system. The operand and operator sequences are highly considered in arithmetic operations in order to perform arithmetic calculations correctly, especially for non-commutative or non-associative operations. This research was conducted to apply the use of Linked List into AR as a method to store the temporary sequence of marker that successfully read by the device then processed again in sequence as simple arithmetic operation using Unity 3D engine aid. From this research also conducted whitebox testing with value of result of cyclomatic complexity is 9, which states the system meets the needs according to the design with low complexity, and usability testing with average SUS yield value is 55 which means the system is not yet feasible for use on the novice user.